Effect of core strength training on C-level difficulty movements of wushu routine athletes - Li, Long (2023)
The C-level difficulty movement refers to the complicated jumping movement stipulated in the wushu rules of the competition set. This study examines the effect of 12 weeks of core strength training on C-level difficulty movements of routine wushu athletes. Forty-two elite wushu athletes, twenty-one (21) in the experimental and 21 in the control groups, respectively, were randomly selected for this study. The core strength training intervention imitated the movement modes of wushu athletes, like run-up, take-off, air spin, and landing stability. In this study, the control group followed the routine training designed by the wushu training center. The experimental group completed 12 weeks of core strength training, 30 minutes per week, and three tests. The pre-test’ was conducted before starting the intervention (week 0), the second test (week 7), and the third test (week 13). For the variables in terms of run-up, take-off, air spin, and landing stability of the Whirl Wind Kick at 720°, the GEE results of the participants revealed that the group had a substantial effect. These results indicate that there was a statistically significant difference in the run-up performance between the groups (2=672,988, p<0.001), take-off (2=787.728, p<0.001), air spin (2= 310.456, p<0.001), and landing stability (2=784,774, p<0.001), respectively. Meanwhile, for run-up, take-off, air spin, and landing stability of the Movement Revolving Turn at 720°, the GEE results of the participants revealed that the group also had a substantial effect. These results indicate that there was a statistically significant difference in the run-up performance between the groups (2=18187.46, p<0.001), take-off (2=28.041, p< 0.001), air spin (2=142031.199, p<0.001), and landing stability (2=41451.042, p<0.001), respectively. For the variables in terms of run-up, take-off, air spin, and landing stability of the Outward Leg Swing in Flight at 720°, the GEE results of the participants revealed that the group had a substantial effect. These results indicate that there was a statistically significant difference in the run-up performance between the groups (2=2753.107, p<0.001), take-off (2=3851.754, p<0.001) air spin (2=16315.333, p<0.001), and landing stability (2=13337.705, p<0.001), respectively. These results showed that the 12-week core strength training significantly improved the C-level difficulty movements of routine wushu athletes. This study can be a source or reference for future researchers who intend to evaluate the effect of core training, especially among wushu players.